2022
DOI: 10.59665/rar3909
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Salicylic Acid Pretreatment on Seedling Growth and Antioxidant Enzyme Activities of Sunflower (Helianthus Annuus L.) and Linseed (Linum Usitatissimum L.) Plants in Salinity Conditions

Abstract: Salinity has become a problem all over the world in agricultural areas. Plants develop a defense mechanism to increase various antioxidant enzyme activities to resist salt stress. In addition, the effects of stress are tried to be reduced with various applications. One of these applications is the application of salicylic acid (SA). However, the effects of SA application vary depending on the plant species and cultivar. In this study, the seeds of sunflower and linseed plants were primed for 4 hours with diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Similarly, in Brassica napus L., Habibi (2015) reported that Se and SA applications enhanced agronomic traits such as pod number, seed number per pod, and seed productivity, potentially by stabilizing carbon dioxide, which positively influences carbon assimilation and subsequent seed formation. Gürsoy (2022) reported that SA application improved sunflower productivity when intercropped with linseed under water-deficit stress by enhancing photosynthetic capacity, CO 2 assimilation, and the release of growth regulators and phytohormones. Similarly, Akbulut (2020) demonstrated that SA application indirectly improved the agronomic traits and seed yield of Jerusalem artichoke (Helianthus tuberosus L.) intercropped with snap bean (Phaseolus vulgaris L.) under water-deficit conditions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Similarly, in Brassica napus L., Habibi (2015) reported that Se and SA applications enhanced agronomic traits such as pod number, seed number per pod, and seed productivity, potentially by stabilizing carbon dioxide, which positively influences carbon assimilation and subsequent seed formation. Gürsoy (2022) reported that SA application improved sunflower productivity when intercropped with linseed under water-deficit stress by enhancing photosynthetic capacity, CO 2 assimilation, and the release of growth regulators and phytohormones. Similarly, Akbulut (2020) demonstrated that SA application indirectly improved the agronomic traits and seed yield of Jerusalem artichoke (Helianthus tuberosus L.) intercropped with snap bean (Phaseolus vulgaris L.) under water-deficit conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the observed increase in proline concentrations following Se and SA treatments suggests the potential of these stress modulators to enhance safflower's stress tolerance mechanisms. Proline accumulation in intercropping systems in plants treated with Se and SA can be attributed to various factors, such as the regulatory influence of abscisic acid (ABA) on light-mediated mechanisms involved in proline metabolism (El-Tohamy et al, 2018) or the presence of highenergy photosynthetic compounds that enhance proline synthesis (Gürsoy, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result of the study, they reported that the content of carotenoids decreased in plants exposed to salt stress, whereas the pigment contents of plants treated with gibberellic acid and proline were at the same level as control plants. Gürsoy (2022b), in her study in which he applied salicylic acid to sunflower and linseed plants under salt stress, reported that pretreatment applications in both plants caused an increase in carotenoid content compared to the control.…”
Section: Carotenoid (Car)mentioning
confidence: 99%